2018
DOI: 10.1210/en.2018-00990
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Progesterone Receptor Isoforms Mediate Opposing Stem Cell and Proliferative Breast Cancer Cell Fates

Abstract: Progesterone receptors (PRs) are key modifiers of estrogen receptor (ER) target genes and drivers of luminal breast cancer progression. Total PR expression, rather than isoform-specific PR expression, is measured in breast tumors as an indicator of functional ER. We identified phenotypic differences between PR-A and PR-B in luminal breast cancer models with a focus on tumorsphere biology. Our findings indicated that PR-A is a dominant driver of cancer stem cell (CSC) expansion in T47D models, and PR-B is a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 83 publications
3
51
1
Order By: Relevance
“…PR-A is a potent driver of stem cell expansion in breast cancer models relative to PR-B, while of the two isoforms, is a stronger driver of proliferation in soft agar (6). These recently published data demonstrated that phosphorylation of PR Ser294 is required for breast cancer stem cell outgrowth as measured in tumorsphere assays and using a variety of breast cancer stem cell markers including CD44+/CD24-and ALDH (6).…”
Section: Stem Cellsmentioning
confidence: 84%
See 4 more Smart Citations
“…PR-A is a potent driver of stem cell expansion in breast cancer models relative to PR-B, while of the two isoforms, is a stronger driver of proliferation in soft agar (6). These recently published data demonstrated that phosphorylation of PR Ser294 is required for breast cancer stem cell outgrowth as measured in tumorsphere assays and using a variety of breast cancer stem cell markers including CD44+/CD24-and ALDH (6).…”
Section: Stem Cellsmentioning
confidence: 84%
“…PR-A is a potent driver of stem cell expansion in breast cancer models relative to PR-B, while of the two isoforms, is a stronger driver of proliferation in soft agar (6). These recently published data demonstrated that phosphorylation of PR Ser294 is required for breast cancer stem cell outgrowth as measured in tumorsphere assays and using a variety of breast cancer stem cell markers including CD44+/CD24-and ALDH (6). PR Ser294 phosphorylation is elevated when the same cells are subjected to 3D relative to 2D culture, as measured using specific antibodies and flow cytometry of permeabilized cells to detect minority PR+ subpopulations (AR Dwyer, TH Truong, and CA Lange, unpublished results).…”
Section: Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations